Replication Dynamics of the Yeast Genome - Raghuraman, M. K.; Winzeler, Elizabeth A.; Collingwood, David; Hunt, Sonia; Wodicka, Lisa; Conway, Andrew; Lockhart, David J.; Davis, Ronald W.; Brewer, Bonita J.; Fangman, Walton L. (Science (American Association for the Advancement of Science), 2001)
Oligonucleotide microarrays were used to map the detailed topography of chromosome replication in the budding yeast Saccharomyces cerevisiae. The times of replication of thousands of sites across the genome were determined by hybridizing replicated and unreplicated DNAs, isolated at different times in S phase, to the microarrays. Origin activations take place continuously throughout S phase but with most firings near mid-S phase. Rates of replication fork movement vary greatly from region to region in the genome. The two ends of each of the 16 chromosomes are highly correlated in their times of replication. This microarray approach is readily applicable to other organisms, including humans.